Prolonged albumin administration in patients with decompensated cirrhosis: the amount makes the difference - Tufoni, Manuel; Zaccherini, Giacomo; Caraceni, Paolo (Annals of Translational Medicine, 2019)
Systemic inflammation and cardiovascular dysfunction represent the main pathophysiological features of decompensated cirrhosis. The “peripheral vasodilation hypothesis” published in 1988 (1) has identified in the arterial vasodilation, mainly occurring in the splanchnic area, the primary cause of the effective hypovolemia, which characterizes the cardiovascular status of patients with decompensated cirrhosis.